Whole‐brain chemical exchange saturation transfer imaging with optimized turbo spin echo readout. Issue 3 (3rd February 2020) - Zhang, Yi; Yong, Xingwang; Liu, Ruibin; Tang, Jibin; Jiang, Hongjie; Fu, Caixia; Wei, Ruili; Hsu, Yi‐Cheng; Sun, Yi; Luo, Benyan; Wu, Dan
Abstract : Purpose: To achieve fast whole‐brain chemical exchange saturation transfer (CEST) imaging with negligible susceptibility artifact. Methods: An optimized turbo spin echo readout module, also known as sampling perfection with application optimized contrasts by using different flip angle evolutions (SPACE), was deployed in the CEST sequence. The SPACE‐CEST sequence was tested in a phantom, 6 healthy volunteers, and 3 brain tumor patients on a 3T human scanner. A dual‐echo gradient echo sequence was used for B0 inhomogeneity mapping. In addition, the proposed SPACE‐CEST sequence was compared with the widely used turbo spin echo‐CEST sequence for amide proton transfer–weighted (APTw) images. Results: The SPACE‐CEST sequence generated highly consistent APTw maps to those of the turbo spin echo‐CEST sequence in the phantom. In healthy volunteers, the SPACE‐CEST sequence yielded whole‐brain 2.8‐mm isotropic APTw source images within 5 minutes, with no discernible susceptibility artifact. As for the B0 maps in the whole brain, its mean, median, and standard deviation B0 offset values were 5.0 Hz, 5.6 Hz, and 16 Hz, respectively. Regarding the APTw map throughout the whole brain, its mean, median, and standard deviation values were 0.78%, 0.56%, and 1.74%, respectively. The SPACE‐CEST sequence was also successfully applied to a postsurgery brain tumor patient, suggesting no disease progression. In addition, on the newly diagnosed brain tumor patients, the SPACE‐CEST and turbo spin echo‐CEST sequences yielded essentially identical APTw values. Conclusion: The proposed SPACE‐CEST technique can rapidly generate whole‐brain CEST source images with negligible susceptibility artifact.